Examining the Properties of Low-luminosity Hosts of Type Ia Supernovae from ASAS-SN - Holoien Thomas WS; Berger Vera L; Hinkle Jason T; Galbany L; Strom Allison L; Vallely Patrick J; Anderson Joseph P; Boutsia Konstantina; French KD; Kochanek Christopher S; Kuncarayakti Hanindyo; Lyman Joseph D; et al. (IOP Publishing Ltd, 2025)
We present a spectroscopic analysis of 44 low-luminosity host galaxies of Type Ia supernovae (SNe Ia) detected by the All-Sky Automated Survey for Supernovae (ASAS-SN), using hydrogen, oxygen, and sulfur emission lines to measure metallicities and star formation rates. We find no statistically significant evidence that the star formation activity and metallicities of the galaxies in our sample are inconsistent with galaxies of similar luminosities and masses. We identify two 3 σ outlier galaxies that have high metallicities for their stellar masses, but find that their other properties are consistent with general galaxies. The overall consistency between our sample and general galaxy samples further strengthens the evidence from more luminous SN Ia host galaxy samples that SN Ia host galaxies are typical.